Analysis of the Relationship Between Phytoplankton Abundance and Total Oil Content in Bayur Bay Waters, Padang City, West Sumatera Province - Ghifari, Muhammad Fadil; Nurrachmi, Irvina; Effendi, Irwan (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
The research was conducted in January - February 2024 in the waters of Teluk Bayur, Padang City, West Sumatra Province. This study analyzes the relationship between total oil content and phytoplankton abundance in Bayur Bay waters. The method used in this study is a survey method with a purposive sampling technique. Based on the results found. The value of oil content at each station and sampling point varies. The highest value is obtained at station III with an average value of 0.00005387 ppm, while the lowest is obtained at station IV with a content value of 0.00001153 ppm. In the Bayur Bay waters, 16 species of phytoplankton were found, consisting of Bacillariophyceae (10 species), Cyanophyceae (2 species), Coscinodiscophyceae (2 species), Dinophyceae (1 species), Raphidophyceae (1 species). Phytoplankton abundance in Bayur Bay waters shows different values for each station, where the highest average phytoplankton abundance is found at station IV, with a total of 9216.55 (ind/L). In contrast, the lowest abundance is found at station I, with a total of 1016.77 (ind/L). The results of linear regression analysis, the relationship between phytoplankton abundance and oil content in Bayur Bay waters at each station obtained a mathematical equation y = 6245.3 + (-7E+07x) with a coefficient of determination R2 = 0.3016 and the correlation coefficient r = 0.5491. With the conclusion that the relationship between phytoplankton abundance and total oil content in Bayur Bay waters is included in the average group.